Achieving Universal Higher Education in China: Characteristics, Challenges, and Future Directions - WANG, ZEYU (Pacific International Journal, 2024)
The universalization of higher education in China has undergone a remarkable transformation driven by government policies and rapid economic growth. This study explores the characteristics and future development of this educational evolution. China’s journey towards universalization began with ambitious policy initiatives in 1998, aiming to expand access to higher education. Within a mere 17 years, the gross enrollment rate in higher education surged from 9.8% to an impressive 50%, surpassing the United States’ 30-year path to universality. This rapid expansion, fueled by a burgeoning economy, has raised questions about educational quality and employability. New universities have played a crucial role, expanding access and optimizing the higher education structure. However, they face challenges due to their short history and limited resources. The study also emphasizes the need for a balanced regional framework and an education model aligning with sustainable development goals. China’s experience in universalizing higher education provides valuable insights for global educational development. This transformation serves as a noteworthy case study, highlighting the importance of balancing quantity and quality in higher education expansion and providing lessons for educational development worldwide.